PENINGKATAN PRESTASI BELAJAR SISWA KELAS III MELALUI PENERAPAN MODEL KOOPERATIF JIGSAW PADA MATA PELAJARAN MATEMATIKA TEMA 8 SD ANAK SHOLEH FULL DAY - YULIA EKA YANTI Yanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The purpose of this study is to determine the application of the Jigsaw learning model in improving learning achievement in thematic subjects of third grade mathematics at SD Anak Sholeh FULL DAY. The type of research used is Classroom Action Research with quantitative and qualitative approaches. The PTK model used is the Kemmis and Mc Taggart model, the researchers carried out research through two cycles, namely cycle I and cycle II. With the following steps: 1) Planning, 2) Implementation, 3) Observation, 4) Reflection. The data collection instruments used include the Student Monkey Sheet (LKS), end-of-cycle test questions, observation sheets for the application of the model, and field notes. The results showed that through the application of the Jigsaw Cooperative Learning model it was proven to be able to improve student achievement. In the first cycle, the percentage increase in learning achievement was 62.50% and in the second cycle it was 84.37%. The results of the N-Gain Score get an average of 2.90 or high category. In the sense of increasing learning achievement in the second cycle increased. It was concluded that learning using the jigsaw cooperative learning model could improve student achievement.